Existence of ground states for fourth-order wave equations - KARAGEORGIS, PASCHALIS (Elsevier, 2010)
Focusing on the fourth-order wave equation utt+?2u+f(u)=0, we prove the existence of ground state solutions u=u(x+ct) for an optimal range of speeds and a variety of nonlinearities f.
PUBLISHED
Keywords: Mathematics; Ground states; Fourth-order wave equations